Kepemilikan Institusional dan Transparansi Informasi terhadap Penghindaran Pajak: Sebelum, Saat, dan Setelah Tax Amnesty - Razali Razali; Ferawati Ferawati (LP2M Universitas Perjuangan Tasikmalaya, 2019)
This study aims to analyze the effect of institutional ownership and transparency of information on tax avoidance before, during, and after tax amnesty. This study uses secondary data obtained from the company’s financial statement of companies listed in Indeks of LQ-45 from 2015-2017 represented timeline of tax amnesty. The data analysis method used in this research is multiple linear regression analysis. Data collected will be processed by using SPSS. The result of this study shows that institutional ownership and transparency of information has no effect on tax avoidance. The highest tax avoidance ratio occured in 2016, when tax amnesty was conducted.